Idiopidae Simon, 1889 in the Brazilian Amazon: two new species and a new geographic record - Gomes, João Pedro Costa; Santos, Naila Amanda Sousa dos; Almeida, Marlus Queiroz; Cipola, Nikolas Gioia; Morais, José Wellington de (EntomoBrasilis, 2024)
Idiopidae Simon, 1889 is mostly composed of spiders known as trapdoor spiders, which create structures for shelter, hunting and protection against possible predators (Mason et al., 2013). It is divided into three subfamilies: Arbanitinae Simon, 1903, with spiders restricted to Oceania, Genysinae Simon, 1903, occurring in India, Sri Lanka, Madagascar and South America, and Idiopinae Simon, 1889, from South America, Africa, East Middle and South to Southeast Asia (Raven 1985; World Spider Catalog 2023). Idiopidae is widely distributed throughout the world, however, only two genera are present in Brazil: Idiops Perty, 1833 and Neocteniza Pocock, 1895. In this work, we describe a new species for both genera present in Brazil and a new record of Idiops.